Global patterns in helminth host specificity: phylogenetic and functional diversity of regional host species pools matter. Issue 3 (16th October 2018) - Wells, Konstans; Gibson, David I.; Clark, Nicholas J.
Abstract : Host specificity has a major influence on a parasite's ability to shift between human and animal host species. Yet there is a dearth of quantitative approaches to explore variation in host specificity across biogeographical scales, particularly in response to the varying community compositions of potential hosts. We built a global dataset of intermediate host associations for nine of the world's most widespread helminth parasites (all of which infect humans). Using hierarchical models, we asked if realised parasite host specificity varied in response to regional variation in the phylogenetic and functional diversities of potential host species. Parasites were recorded in 4–10 zoogeographical regions, with some showing considerable geographical variation in observed versus expected host specificity. Parasites generally exhibited the lowest phylogenetic host specificity in regions with the greatest variation in prospective host phylogenetic diversity, namely the Neotropical, Saharo‐Arabian and Australian regions. Globally, we uncovered notable variation in parasite host shifting potential. Observed host assemblages for Hydatigera taeniaeformis and Hymenolepis diminuta were less phylogenetically diverse than expected, suggesting limited potential to spillover into unrelated hosts. Host assemblages for Echinococcus granulosus, Mesocestoides lineatus and Trichinella spiralis were less functionally diverse than expected, suggesting limited potential to shift across host ecological niches. By contrast, Hyd. taeniaeformis infected a higher functional diversity of hosts than expected, indicating strong potential to shift across hosts with different ecological niches. We show that the realised phylogenetic and functional diversities of infected hosts are determined by biogeographical gradients in prospective host species pools. These findings emphasise the need to account for underlying species diversity when assessing parasite host specificity. Our framework to identify variation in realised host specificity is broadly applicable to other host–parasite systems and will provide key insights into parasite invasion potential at regional and global scales.